2021
DOI: 10.1016/j.isci.2021.103132
|View full text |Cite
|
Sign up to set email alerts
|

Pioneer factors in development and cancer

Abstract: Summary Transcription factors (TFs) are essential mediators of epigenetic regulation and modifiers of penetrance. Studies from the past decades have revealed a sub-class of TF that is capable of remodeling closed chromatin states through targeting nucleosomal motifs. This pioneer factor (PF) class of chromatin remodeler is ATP independent in its roles in epigenetic initiation, with nucleosome-motif recognition and association with repressive chromatin regions. Increasing evidence suggests that the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 181 publications
(227 reference statements)
3
24
0
Order By: Relevance
“…Strikingly, we found that the mesodermal factor MyoD1 was most potent in imposing its fate and repressing the original mesodermal fibroblast identity. This might seem surprising since not only MyoD1 but also Ascl1, FoxA2, Sox2, and Oct4 have been attributed pioneer factor activity and are all considered key drivers of their respective reprogramming paradigms (Iwafuchi‐Doi & Zaret, 2014 ; Zaret & Mango, 2016 ; Zaret, 2020 ; Sunkel & Stanton, 2021 ). Indeed, Ascl1 and MyoD1 are, on their own, sufficient to reprogram MEFs into induced neurons and muscles, respectively (Davis et al , 1987 ; Chanda et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, we found that the mesodermal factor MyoD1 was most potent in imposing its fate and repressing the original mesodermal fibroblast identity. This might seem surprising since not only MyoD1 but also Ascl1, FoxA2, Sox2, and Oct4 have been attributed pioneer factor activity and are all considered key drivers of their respective reprogramming paradigms (Iwafuchi‐Doi & Zaret, 2014 ; Zaret & Mango, 2016 ; Zaret, 2020 ; Sunkel & Stanton, 2021 ). Indeed, Ascl1 and MyoD1 are, on their own, sufficient to reprogram MEFs into induced neurons and muscles, respectively (Davis et al , 1987 ; Chanda et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 5, 2022. ; https://doi.org/10.1101/2022.12.05.519166 doi: bioRxiv preprint structural domains (40,41). These data suggest that the master regulatory factors PAX3-FOXO1 and MYOD have distinct chromatin structural roles in RMS, as opposed to overlapping functions.…”
Section: Association With Transcription Factors and Histone Marksmentioning
confidence: 93%
“…Chromatin samples were immunoprecipitated overnight at 4 C with antibodies targeting MYOD (CST cat#13812S), H3K27ac (Active Motif, cat#39133). DNA purifications were performed with modified ChIP protocol described previously 40 . For sample normalization 2 million C2C12 cells of were added to 6 million RMS cells before sonication.…”
Section: Methodsmentioning
confidence: 99%
“…PFs engage with nucleosomes [ 33 ] that are dynamically transitioning between fully wrapped and transient exposure states [ 34 , 35 ]. The window of exposure is sufficient to allow binding of PFs as well as other TFs [ 36 ]. PFs typically bind to poised/active enhancers containing histone marks such as histone 3 lysine 4 mono/di-methylation (H3K4me1/me2) [ 37 , 38 ] and histone 3 lysine 9/27 acetylation (H3K9/27ac) [ 39 , 40 ].…”
Section: Pioneer Factors and Dna Bindingmentioning
confidence: 99%
“…This is strongly influenced by AR itself, as those sites that are unaffected following FOXA1 knockdown generally have higher AR occupancy [ 54 ]. GATA2 (GATA-binding factor 2) is another well-characterized PF that increases accessibility at ARBS [ 36 , 55 ]. Although GATA2 chromatin accessibility induction is less effective than FOXA1 [ 52 ], GATA proteins facilitate binding of AR and estrogen receptor (ER) in prostate [ 56 ] and breast cancer [ 57 ], respectively.…”
Section: Pioneer Factors and Dna Bindingmentioning
confidence: 99%